The Improvement of the Dissolution and Release Characteristics of Ibuprofen Suppository Through Inclusion Complexes with - Darusman, F.; I. Septian, M.; Kartadarma, E. (KnE Life Sciences, 2022)
Ibuprofen is classified as a BCS class II because of its low solubility and high permeability. Inclusion complex formation using β-cyclodextrin is one method to increase a drug’s solubility. In addition to the method of increasing the solubility, the choice of dosage form and route of administration has a big role in the success of therapy because it can increase the onset of action of drugs while avoiding side effects. Rectal suppositories can provide a faster antipyretic effect than oral preparations. The purpose of this study was to determine the effect of inclusion complexes formation with β-cyclodextrin in increasing the dissolution rate and release characteristics of ibuprofen suppositories. The suppository formulation used various concentrations of cetylalcohol to increase the consistency of the cocoa butter base. The release characteristics of ibuprofen in suppositories were evaluated, including, organoleptic, melting time, weight diversity, dissolution rate and dissolution efficiency, by comparing ibuprofen inclusion complex suppositories with β-cyclodextrin all three mole ratios, namely 1:1, 1:2 and 2:1, to pure ibuprofen suppositories. The inclusion complex of ibuprofen with β-cyclodextrin at a mole ratio of 2:1 showed to increase the solubility and dissolution rate of ibuprofen in suppositories with good physical and release characteristics. Keywords: ibuprofen, inclusion complexes, suppository